Digital suction and family functionality in children in Health Area II. Cienfuegos. - Ana María Nápoles Quintero; Omaida Borroto Abal; Nora Sexto Delgado; Anay Valladares González; Raúl López Fernández; Lourdes Martínez Casanova (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2007)
Bakground: Digital suction is a pernicious habit that can produce not only alterations of dental-facial's structures, but also of child's social relationships and its self-esteem. Objective: To evaluate the existent relationship between finger suction habit in children and family functionality. Method: An analytic study of cases and controls was carried out, in girls and boys of 5th and 6th levels in 8 day-care centres belonging to Area II of Cienfuegos municipality during the course 2005-2006. The studied variables were: finger suction habit, age, level, sex, and family functionality. Family functionality was perceived through the test FF-SIL. Chi square test was used to determine the relationship among the studied variables. Results: The finger suction habit prevailed in girls; functional families prevailed in the study. Most of the children with this habit come from dysfunctional families. Conclusion: Dysfunctional and severely dysfunctional families are proportionally major in the group of girls and boys with this habit, being shown the dependence between the variables finger suction and family function.